Benefits of a disease management program for Sickle Cell Disease in Germany 2011-2019: the increased use of hydroxyurea correlates with a reduced frequency of acute chest syndrome - Kunz, Joachim; Schlotmann, Andreas; Daubenbüchel, Andrea; Lobitz, Stephan; Jarisch, Andrea; Grosse, Regine; Cario, Holger; Oevermann, Lena; Hakimeh, Dani; Tagliaferri, Laura; Kulozik, Andreas (Journal of Clinical Medicine, 2021)
Sickle Cell Disease (SCD) is the most common monogenic disorder globally but qualifies as a rare disease in Germany. In 2012, the German Society for Paediatric Oncology and Haematology (GPOH) mandated a consortium of five university hospitals to develop a disease management program for patients with SCD. Besides other activities, this consortium issued treatment guidelines for SCD that strongly favour the use of hydroxyurea and propagated these guidelines in physician and patient education events. In order to quantify the effect of these recommendations, we made use of claims data that were collected by the research institute (WIdO) of the major German insurance company, the Allgemeine Ortskrankenkasse (AOK), and of publicly accessible data collected by the Federal Statistical Office (Statistisches Bundesamt, Destatis). While the number of patients with SCD in Germany increased from approximately 2200 in 2011 to approximately 3200 in 2019, important components of the recently issued treatment guidelines have been largely implemented. Specifically, the use of hydroxyurea has more than doubled, resulting in a proportion of approximately 44% of all patients with SCD being treated with hydroxyurea in 2019. In strong negative correlation with the use of hydroxyurea, the frequency of acute chest syndromes decreased. Similarly, the proportion of patients who required analgesics and hospitals admissions declined. In sum, these data demonstrate an association between the dissemination of treatment guidelines and changes in clinical practice. The close temporal relationship between the increased use of hydroxyurea and the reduction in the incidence of acute chest syndrome in a representative population-based analysis implies that these changes in clinical practice contributed to an improvement in key measures of disease activity.
Gesehen am 27.01.2022
This article belongs to the special issue "Acute and chronic sickle cell disease: causes, consequences, and treatment"